2021
DOI: 10.1093/rheumatology/keab214
|View full text |Cite
|
Sign up to set email alerts
|

The use and context of the term ‘multimorbidity’ in rheumatoid arthritis: a systematic literature review

Abstract: This systematic literature review aimed to analyse term(s) describing co-existing conditions in rheumatoid arthritis (RA) literature, informing the need for an operationalised definition of multimorbidity. Articles discussing RA with multimorbidity, published 1946 until August 2020, were identified. The primary outcome was use and/or definition of “multimorbidity” in RA. Information extracted included: term(s) defining co-existing conditions; use of comorbidity/multimorbidity score; use of “inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
3
0
2
Order By: Relevance
“…Multimorbidity is often used interchangeably with comorbidity, the expressions can be distinguished by the fact that in the definition of multimorbidity a dominant disease is nonexistent [ 15 ]. In this study, patients are defined as multimorbid when suffering from RA and at least one other chronic disease as defined by the Elixhauser Comorbidity index [ 16 , 17 ]. Comorbidity indices are generally applied to predict the mortality, hospitalization and functioning of patients by considering the level of comorbidity [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Multimorbidity is often used interchangeably with comorbidity, the expressions can be distinguished by the fact that in the definition of multimorbidity a dominant disease is nonexistent [ 15 ]. In this study, patients are defined as multimorbid when suffering from RA and at least one other chronic disease as defined by the Elixhauser Comorbidity index [ 16 , 17 ]. Comorbidity indices are generally applied to predict the mortality, hospitalization and functioning of patients by considering the level of comorbidity [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…The above findings on CVD risk factors highlight the interplay of coexisting conditions. As Dey et al suggested for RA, we may need to move away from the term comorbidity, indicating the presence of an index disease as the center of interest, and focus on the concept of multimorbidity where all diseases are managed equally, and a comprehensive approach to care is considered [128].…”
Section: Cardiovascular Risk Factorsmentioning
confidence: 99%
“…Як відомо, ураження серцево-судинної системи у дорослих із РЗ -це перш за все розвиток хронічної серцевої недостатності та атеросклеротичних уражень коронарних судин із розвитком інфаркту міокарда, хронічної ішемічної хвороби серця або ішемічних проявів з боку периферичних судин [4,5]. У зв'язку з цим розроблено рекомендації з профілактики кардіоваскулярного ризику у хворих із ревматоїдним артритом [18].…”
Section: результати та обговоренняunclassified
“…За рахунок системного ураження ендотелію судин відбувається розвиток не тільки клінічних проявів основного процесу, але й формування уражень структур життєво важливих органів і систем (кардіоміоцити, гепатоцити, нейрони, нефрони тощо), розвиток фіброзних процесів із формуванням недостатності органів (серцево-судинної і бронхолегеневої систем, нирок, печінки тощо), метаболічних порушень, зокрема в ліпідному спектрі крові, вуглеводному і в системі гемостазу. Усе це впливає на перебіг основного захворювання, погіршує відповідь на терапію, знижує якість життя пацієнтів, ускладнює прогноз [4].…”
unclassified